CONTEMPORARY APPROACHES TO MASTERING PRACTICAL SKILLS - Tovasharov Mukhammadali Yuldashevich; Sokhibov Oybek Mardonovich (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Purpose of the Presentation: This presentation demonstrated that practical skills can be developed 2–5 times faster and with 70–80% real-world transfer effectiveness using modern methods (deliberate practice, ecological dynamics, VR/AR/AI). Additionally, the triad model and practical recommendations applicable directly in educational institutions in Uzbekistan are presented. Research Methods: The study employed theoretical analysis, comparative analysis, synthesis of international experience, a systematic review and meta-analysis covering 182 empirical studies conducted between 2020 and 2025, three real case studies in Uzbekistan and abroad (medical education, vocational training, sports), semi-structured interviews with teachers and trainers, and synthesis methods. All statistical analyses were conducted using Hedges’ g effect size.